Discourse analysis : an introduction - Georgakopoulou, Alexandra (Edinburgh University Press, 2004)
A clear and lively introduction to current trends in the theory, method and tools of discourse studies, this book is a valuable guide for students and teachers of linguistics as well as for those with an interest in the linguistic methods of analysing discourse (media, rhetoric and stylistics, pragmatics, communication studies scholars etc). Comprehensive, accessible, state-of-the-art textbook Close analyses of a wide range of narrative and non-narrative texts, both spoken and written Emphasis on practical text analysis: includes guided activities for self-study or use in a classroom Suggestions for further reading in each chapter. This revised second edition registers key changes in a rapidly expanding area and thoroughly updates suggestions for further reading and the bibliography.